From Verse to Praxis: An Eco-Theological Exegesis of Qur'anic Educational Verses for a Love-Based Pedagogy - Rohman, Muhamad Asvin Abdur (Jurnal Ushuluddin, 2025)
Thisarticle aims to examine the concept of love-based education in the Qur'an through an eco-theological interpretation of educational verses.In this study, theconcept of "love" is specifically understood as raḥmah (universal compassion), which serves as the ontological foundation of creation and revelation, rather than merely ḥubb (specific, preferential love). The research employs a thematic exegesis (tafsīr mawdhū‘ī) approach,analyzingkey verses related to education, raḥmah, and the human-naturerelationshipthrough thelensesof eco-theology and contemporary Islamic education. The findings reveal that Qur'anic education is deeply rooted in raḥmah as the ontological and ethical foundation for the relationship between God, humanity, and nature. The concept of human vicegerency (khalīfah fī al-arḍ) is understood as a moral and educational mandate to preserve ecological balance,rather than as a justificationfor environmental exploitation. Based on these findings, this article formulates a Raḥmah-Based Education Frameworkfrom the perspectiveof Qur'aniceco-theology,encompassing theological, pedagogical, and ecological dimensions. This study affirms that an Islamic education paradigm oriented towards love (raḥmah) and ecological consciousness has the potential toserve asan alternativeframework for addressingthe global environmental crisis and for shaping learners who are faithful, virtuous, and responsiblestewards of life’s sustainability.